Relation of plasma high-density lipoproteins-cholesterol with sarcopenia in patients with chronic obstructive pulmonary disease - Walid Abu-Libdeh; Jeneen Khrais; Laith Suwan; Fares Hamdan; Ahmad Qandil; Aya Abdelfattah Kaml; Ghaith Alsabbagh; Said Alsaied; Mohamed Feras Ebedin; Sahar O Aburuf; Manahil A Bakir; Razan A Awad; et al. (Indian Journal of Respiratory Care, 2022)
Background: Plasma high-density lipoproteins-cholesterol (HDL-C) is a marker of metabolic health; however, its association with age-associated muscle loss, termed sarcopenia, is unknown. We evaluated the clinical importance of HDL-C in predicting sarcopenia in patients with chronic obstructive pulmonary disease (COPD). Methods: We investigated male healthy elderly and COPD patients, 54–79 years old (n = 55–59/group) through clinical examination, laboratory investigation, and spirometry. Sarcopenia was evaluated as low handgrip strength (HGS), appendicular skeletal mass index (ASMI), and gait speed. Enzyme-linked immunosorbent assays were used to measure the circulating markers of inflammation (C-reactive protein [CRP]) and oxidative stress (8-isoprostanes). Results: The COPD patients exhibited reduced HGS, ASMI and gait speed, and higher CRP and 8-isoprostanes levels and incidence of sarcopenia than controls (all P < 0.05). Plasma HDL-C levels exhibited significant correlations with CRP, HGS, and 8-isoprostane levels (all P<0.05) but not with ASMI and gait speed in both cohorts. Additionally, plasma HDL-C was an independent predictor of sarcopenia in controls and COPD patients (AUC = 0.631, P<0.05). Conclusion: Altogether, our data show that plasma HDL-C levels are a valuable marker of muscle decline and sarcopenia in healthy elderly and patients with COPD.